2019 IEEE International Conference on Networking, Architecture and Storage (NAS) 2019
DOI: 10.1109/nas.2019.8834720
|View full text |Cite
|
Sign up to set email alerts
|

Learning Workflow Scheduling on Multi-Resource Clusters

Abstract: Workflow scheduling is one of the key issues in the management of workflow execution. Typically, a workflow application can be modeled as a Directed-Acyclic Graph (DAG). In this paper, we present GoDAG, an approach that can learn to well schedule workflows on multi-resource clusters. GoDAG directly learns the scheduling policy from experience through deep reinforcement learning. In order to adapt deep reinforcement learning methods, we propose a novel state representation, a practical action space and a corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One other work used A3C (Asynchronous Advantage Actor-Critic) and residual neural network for scheduling stochastic edge-cloud environment [239]. some work also used the same RL model for workflow scheduling [240,241].…”
Section: Reinforcement Learning Techniques For Edge Ai Managementmentioning
confidence: 99%
“…One other work used A3C (Asynchronous Advantage Actor-Critic) and residual neural network for scheduling stochastic edge-cloud environment [239]. some work also used the same RL model for workflow scheduling [240,241].…”
Section: Reinforcement Learning Techniques For Edge Ai Managementmentioning
confidence: 99%
“…Mao et al reported the advances of their RL-based solutions [18]. However, in those works, the robustness of the solution is often a big obstacle for utilizing those solutions in a new operating environment where workloads of the requests are different from the training data [19].…”
Section: Introductionmentioning
confidence: 99%